Translational ADMET for drug therapy : principles, methods, and pharmaceutical applications - Yanni, Souzan (Hoboken, New Jersey : John Wiley & Sons, Inc., 2015)
Serving as a practical handbook about ADMET for drug therapy, this book presents effective technologies, methods, applications, data interpretation, and decision-making tactics for pharmaceutical and preclinical scientists. Chapters cover case studies and in vivo, in vitro, and computational tools for drug discovery and development, with new translational approaches to clinical drug investigations in various human populations. -Illustrates ADME properties, from bedside to bench and bench to bedside, for the design of safe and effective medicine in human populations -Provides examples that demonstrate the integration of in vitro, in vivo, and in silico data to address human PKPD and TKTD and help determine the proper therapeutic dosage -Presents successful tools for evaluating drugs and covers current translational ADMET with regulatory guidelines -Offers a hands-on manual for researchers and scientists to design and execute in vitro, in silico, preclinical, and clinical studies -Includes discussion of IND / NDA filing and drug labeling to support drug registration and approval.
Translational Concept and Determination of Drug Absorption -- Distribution: Principle, Methods, and Applications -- Metabolism: Principle, Methods, and Applications -- Excretion: Principle, Methods, and Applications for Better Therapy -- Drug-Drug Interaction: From Bench to Drug Label -- General Toxicology: Principle, Methods, and Applications -- Toxicokinetics and Toxicity Testing in Drug Development -- PBPK Modeling and In Silico Prediction for ADME and Drug-Drug Interaction -- Translational Tools toward Better Drug Therapy in Human Populations -- Phase 1-Phase 3 Clinical Studies, Procedures, Responsibilities, and Documentation -- Regulatory Submission: MIST and Drug Safety Assessment.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Pharmacokinetics; Drugs -- Metabolism -- Pharmacokinetics; Drug Evaluation, Preclinical; Pharmacokinetics; Drug-Related Side Effects and Adverse Reactions; Pharmaceutical Preparations -- metabolism; Medical; Electronic books